Gender dan Usia dalam Memoderasi Pengalaman dan Kepercayaan Merek terhadap Loyalitas Shopee - Siti Barokah; Andrian Abimanyu; Eka Riyana (Jurnal Manajemen Bisnis Performa, 2020)
ABSTRACTThe emergence of online shops involved in competition between merchants in cyberspace. So, that online merchants complete with each other to keep their customers. The effort made is studying the factors that can increase customer loyalty attitudes. This research is a quantitative study using the online survey method. The sample in this study were all customers of the online shopee shopping site. The variables used in this study are brand experience, brand trust, and brand loyalty. In addition, this study also uses moderating variables, namely gender and age. The sampling technique in this research is purposive sampling. Data analysis show that the shoppe experience and online shopping site trust have a positive influence on shopee online shopping site loyalty. In addition, gender and age also merate the influence of experience and trust on shopee online shopping site loyalty. Keywords: Brand Experience, Brand Trust, Brand Loyalty, Gender, Age.